2007
DOI: 10.1681/asn.2007010044
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Prevent Progressive Experimental Renal Failure but Maldifferentiate into Glomerular Adipocytes

Abstract: Glomerulonephritis (GN) isM esenchymal stem cells (MSC) hold special promise for renal repair, because nephrons are largely of mesenchymal origin (1). The potential of MSC for renal repair has been shown in rodent models of acute renal failure (ARF), where the course of glycerol, cisplatin, or ischemia-reperfusion induced ARF was improved by MSC injection shortly after disease induction (2-5). In addition, we recently reported that injection of rat MSC into a renal artery can accelerate recovery from mesangiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
165
2
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 258 publications
(186 citation statements)
references
References 41 publications
9
165
2
10
Order By: Relevance
“…Indeed, several studies have examined the possibility that bone-marrow-derived stem cells might be used for renal repair. [32][33][34][35][36] However, their beneficial role can be offset by their abnormal local differentiation into adipocytes accompanied by glomerular sclerosis. 33 In conclusion, the results of this study provide the first demonstration that glomerular injury can be repaired by using resident renal progenitor cells and suggest that the kidney might contain a "renopoietic system" ( Figure 6) with a bipotent progenitor localized at the urinary pole of Bowman's capsule, where it can initiate the replacement and regeneration of glomerular and tubular epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have examined the possibility that bone-marrow-derived stem cells might be used for renal repair. [32][33][34][35][36] However, their beneficial role can be offset by their abnormal local differentiation into adipocytes accompanied by glomerular sclerosis. 33 In conclusion, the results of this study provide the first demonstration that glomerular injury can be repaired by using resident renal progenitor cells and suggest that the kidney might contain a "renopoietic system" ( Figure 6) with a bipotent progenitor localized at the urinary pole of Bowman's capsule, where it can initiate the replacement and regeneration of glomerular and tubular epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, evidence from murine studies has indicated that MSCs could maldifferentiate in glomerular adipocytes once injected in a rat model of progressive glomerulonephritis. 39 One possible alternative to the MSC infusion in organ transplantation might be MV treatment. One advantage of using MVs rather than the MSCs themselves is to avoid possible long-term maldifferentiation of engrafted cells or tumor generation.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Some studies have shown improvement after MSC delivery in a model of glomerulonephropathy [54] and no evidence of a long-term fibrotic response 3 months after delivery of MSCs to animals with severe AKI [44]. Other studies have suggested that the beneficial effects linked to MSC injection can be marred by a long-term partial maldifferentiation of intraglomerular MSCs into adipocytes accompanied by glomerular sclerosis in a model of chronic glomerulonephritis [55]. Other studies have shown that in models of glomerular injury MSCs have no beneficial effect.…”
Section: Mesenchymal Stromal Cells (Mscs)mentioning
confidence: 99%